Comparative efficacy of radiofrequency denervation in chronic low back pain: A systematic review and network meta-analysis - Li, Han; An, Junyan; Zhang, Jun; Kong, Weijian; Yun, Zhihe; Yu, Tong; Nie, Xinyu; Liu, Qinyi (Frontiers in Surgery, 2022)
Background Facet joint pain is a common cause of chronic low back pain (CLBP). Radiofrequency (RF) denervation is an effective treatment option. Purpose A systematic review and network meta-analysis (NMA) was performed to evaluate and compare the efficacy and effectiveness of different RF denervation treatments in managing facet joint-derived CLBP. Methods The Cochrane Library, Embase, PubMed, and China Biology Medicine were searched to identify eligible randomized controlled trials (RCTs) from January 1966 through December 2021. Interventions included conventional radiofrequency denervation (CRF), pulsed radiofrequency denervation (PRF), pulsed radiofrequency treatment of the dorsal root ganglia (PRF-DRG), radiofrequency facet capsule denervation (RF-FC), and radiofrequency ablation under endoscopic guidance (ERFA). The outcome was the mean change in visual analog scale (VAS) score from baseline. A random-effects NMA was used to compare the pain relief effects of the interventions over the short term (≤6 months) and long term (12 months). The rank of effect estimation for each intervention was computed using the surface under the cumulative ranking curve. Results A total of 10 RCTs with 715 patients met the inclusion criteria. Moderate evidence indicated that CRF denervation had a greater effect on pain relief than sham control in the short term (standardized mean difference (SMD) −1.58, 95% confidence intervals (CI) −2.98 to −0.18) and the long term (SMD −4.90, 95% CI, −5.86 to −3.94). Fair evidence indicated that PRF denervation was more effective than sham control for pain over the long term (SMD −1.30, 95% CI, −2.17 to −0.43). Fair evidence showed that ERFA denervation was more effective for pain relief than sham control in the short term (SMD −3.07, 95% CI, −5.81 to −0.32) and the long term (SMD −4.00, 95% CI, −4.95 to −3.05). Fair evidence showed that RF-FC denervation was more effective for pain relief than sham control in the long term (SMD −1.11, 95% CI, −2.07 to −0.15). A fair level of evidence indicated that PRF-DRG denervation was more effective for pain relief than sham control in the short term (SMD −5.34, 95% CI, −8.30 to −2.39). Conclusion RF is an effective option for patients diagnosed with facet joint-derived CLBP. Systematic Review Registration: Identifier: CRD42022298238.